¿Nueva era de proteccionismo?: El papel de los Acuerdos de Libre Comercio en América Latina - Arrieta, Gabriel (2017)
After the accession of Donald Trump as president of the United States, the recent protectionist trade environment is guarantee that the American trade policy could affect Latin American countries, due to the importance of United States as trading partner. These policies would not only affect Latin American countries, but also their main trading partners as China, that could respond with other protectionist policies, which could lead to the beginning of a domino effect, where the biggest loser could be Latin America. Taking into account the current international context, in this article it will be making policy recommendations on Free Trade Agreement issues aimed to reducing the possible impacts of American trade policies in Latin American countries (especially, considering the recent United States’ withdraw from the Trans-Pacific Partnership deal).